The Palgrave Handbook of Religion and State Volume II Global Perspectives - Holzer, Shannon (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
The Palgrave Handbook of Religion and State Volume II: Global Perpectives addresses issues of Religion and State from a multitude of disciplines. The volume begins with the philosophical discussion of perennial issues that have to do with the origin and nature of rights. One question centers on the right to use one's religious beliefs to enact laws. This discussion alone sets this handbook apart from other handbooks of its type. While addressing these perennial questions, this volume includes authors who interact with the work of John Rawls, Hobbes, Rousseau, and a host of contemporary philosophers. The subsequent sections address the American Constitutional Experiment, religion, state, and law in the Americas.
1: Introduction -- Part 1: Religion and State in Philosophy -- Chapter 2: Religious Reasons in Political Discourse -- Chapter 3: A Plantingan Response to Public Reason Accessibilism -- Chapter 4: Matters of Conscience -- Chapter 5: On the Definition of Religious Belief -- Chapter 6: Natural Law and the American Founding -- Part 2: Religion and the American Constitutional Experiment -- Chapter 7: Why Do We Think the Framers Wanted to Separate Church and State?- Chapter 8: American Church - State Relations: Jefferson's Conception of Religious Freedom -- Chapter 9: A Liberal and Generous Toleration: John Adams and the Freedom for Religion -- Chapter 10: Nondiscrimination or Accommodation?: Two Competing Visions of the Free Exercise Clause -- Chapter 11: In Praise of Separationism: A Lamentation on the Demise of that Famous Paragraph in Everson v. Board of Education -- Chapter 12: The Requirement of Church and State to be Forever Separate -- Chapter 13: Why Church and State Should be Kept Separate but Politics and Religion Should Not -- Chapter 14: Is Religion Serious Enough to Be Taken Seriously?- Chapter 15: Does the Separation of Church and State Require Secularism?- Chapter 16: Miltonic Liberty and the Grounds for Disestablishment in A Treatise of Civil Power -- Chapter 17: A Marriage of Opposites: Tocqueville on Religion and Democracy -- Chapter 18: Public Spirit as Mediating Influence Between Tocqueville's "Spirit of Religion" and "Spirit of Freedom" -- Part 3: Religion and Law in the American Courts -- Chapter 19: Testing Neutrality: The Courts' Use of Legal Tests in Determining Establishment and Free Exercise Cases -- Chapter 20: Corporate Religious Liberty After Hobby Lobby -- Chapter 21: The Ministerial Exception and the Distinction between Church and State -- Chapter 22: The Definition of Marriage from Reynolds to Obergefell -- Chapter 23: The Separation of Church and State: The Court's 'Secular Purpose' and the Argumentum ex Ignorantia -- Chapter 24: Changes in Conscience Clauses and the Effect on Religious Affiliated Hospitals and Health Care Practitioners -- Chapter 25: Title: A Very Private, Very Public Matter: Contraception and Religious Freedom -- Chapter 26: Religion and Education: A New Birth of Freedom for Unsettled Times -- Chapter 27: The Global State Church: The Political and Security Roles of Religion in Contemporary Education -- Chapter 28: Sexual Identity, Gender Ideology, and Religious Freedom: The Tug of War over "Who We Are" Schools as Battlegrounds -- Part 4: Religion and the State in Canada, Mexico, and South America -- Chapter 29: Religion and State in Canada Janet Epp Buckingham -- Chapter 30: Religion and State in Mexico Roberto Blancart -- Chapter 31: Religion and State in Colombia -- Chapter 32: Religion and State in Argentina -- Chapter 33: Religion and State in Brazil Rodrigo Alves, The Brazilian Center of Studies in Law and Religion -- Chapter 34: Religion and State in Chile -- Chapter 35: Religion and State in the Caribbean.
Keywords: Religions; America; Religion and politics; Religion and law; American Religions; Politics and Religion; Law and Religion